The Russians are Coming The Bolshoi's radical new Romeo and Juliet seen in Moscow - Craine, Debra (Dance Books Ltd., Alton,Hampshire (UK), 2004)
The Bolshoi's new Romeo and Juliet. Ratmansky sees it as his brief to ensure that the Bolshoi is fertile ground for new choreography. PALABRAS CLAVE: Bolshoi Ballet, Declan Donnellan, Romeo and Juliet, Moldovan Radu Poklitaru, Alexei Ratmansky.